Effects of Climate Change on Peatland Reservoirs: A DOC Perspective. Issue 7 (21st July 2021) - Fenner, N.; Meadham, J.; Jones, T.; Hayes, F.; Freeman, C.
Abstract: Peatland reservoirs are global hotspots for drinking water provision and are likely to become more important as demand per capita rises and the climate changes. Dissolved organic carbon (DOC) is associated with harmful disinfection byproducts and reduced aesthetic quality, and its removal is the major treatment cost. Littoral zones are known to be disproportionately important for DOC production through macrophyte inputs, and such communities are predicted to expand with warming in northern regions. However, little is known about autochthonous DOC contributions and their response to climatic change. Here we exposed mesocosms to elevated CO2 (eCO2 ), warming and a combined treatment across a trophic gradient. Regression analysis indicated that while sediments, macrophytes, and phytoplankton are important DOC sources ( P  < 0.05), benthic algal biomass showed the strongest relationship with DOC ( P  < 0.05), suggesting it is an underestimated source. DOC removal indicators, namely phenol oxidase (depolymerization) and respiration (mineralization) were inversely related to DOC concentration in oligohumic ( P  < 0.05) and oligotrophic ( P  < 0.1) systems, suggesting heterotrophic processes are important in DOC removal. DOC concentrations increased across all systems ( P  < 0.05), irrespective of trophic status, due to increased photoautotrophic inputs (macrophyte, pelagic, and benthic algae) under eCO2, warming, and combined scenarios, with inhibited depolymerization and mineralization under eCO2, even when combined with warming ( P  < 0.05 and P  < 0.05 excepting the oligo‐mesotrophic reservoir P  < 0.1 respectively). Increased DOC loads of all fractions, regardless of provenance, are predicted in a future climate and, thus, investment in techniques to remove a greater range of DOC fractions is proposed to help "future proof" drinking water supplies. Plain Language Summary: Peatlands form in wet areas and therefore are important sources of drinking water in many regions. The waterlogged conditions prevent decomposition of plant material and allow vast stores of carbon to accumulate as peat. Dissolved carbon leaches from these stores and into peatland reservoirs. This is a problem for the water treatment industry because the carbon interacts with chlorine used to disinfect our water, causing harmful byproducts. Algae and aquatic plants within reservoirs also produce dissolved carbon, while microbes consume it. However, little is known about how important these sources and sinks are, or how climate change might affect them, and therefore the treatability of our water. We used reservoir mesocosms exposed to elevated CO2, warming, and combined climate change simulations to investigate this. Algal carbon sources were greater than expected, which is important because they can be associated with particularly toxic treatment byproducts. We also found that plant and algal production increased under all climate change scenarios, while microbial removal was inhibited, giving higher levels of dissolved carbon, but also a greater range of types and sizes. These results suggest that more efficient and varied treatment processes are needed to help future proof drinking water quality from peaty catchments. Key Points: Benthic algal production represents an underestimated dissolved organic carbon source in peatland reservoirs Phytoplankton dissolved organic carbon contributions may be more important in low productivity systems than expected Increased dissolved organic carbon loads of all fractions are predicted at drinking water treatment works in a future climate